Location and Number of Selenium Atoms in Two-Dimensional Conjugated Polymers Affect Their Band-Gap Energies and Photovoltaic Performance - Jiang, Jian-Ming; Raghunath, Putikam; Lin, Hsi-Kuei; Lin, Yu-Che; Lin, M. C; Wei, Kung-Hwa (Macromolecules, 2014)
We synthesized and characterized a series of novel two-dimensional Se-atom-substituted donor (D)−π-acceptor (A) conjugated polymersPBDTTTBO, PBDTTTBS, PBDTTSBO, PBDTSTBO, PBDTTSBS, PBDTSTBS, PBDTSSBO, and PBDTSSBSfeaturing benzodithiophene (BDT) as the donor, thiophene (T) as the π-bridge, and 2,1,3-benzooxadiazole (BO) as the acceptor with different number of Se atoms at different π-conjugated locations, including the π-bridge, side chain, and electron-withdrawing units. We then systematically investigated the effect of different locations and the number of Se atoms in these two-dimensional conjugated polymers on the structural, optical, and electronics such as band-gap energies of the resulting polymers, as determined through quantum-chemical calculations, UV–vis absorption spectra, and grazing-incidence X-ray diffraction. We found that through the rational structural modification of the 2-D conjugated Se-substituted polymers the resulting PCEs could vary over 3-fold (from 2.4 to 7.6%), highlighting the importance of careful selection of appropriate chemical structures such as the location of Se atoms when designing efficient D−π-A polymers for use in solar cells. Among these tested BO-containing polymers, PBDTSTBO that has moderate band gaps and good open-circuit voltages (up to 0.86 V) when mixed with PC71BM (1:2, w/w) provided the highest power conversion efficiency (7.6%) in a single-junction polymer solar cell, suggesting that these polymers have potential applicability as donor materials in the bulk heterojunction polymer solar cells.